Hubungan Self-Care dengan Kepatuhan Minum Obat Pada Penderita Hipertensi - Shela Handayani; Vincencius Surani; Keristina Ajul; Lilik Pranata (Jurnal Keperawatan Florence Nightingale, 2024)
The serious impact of hypertension is that it can cause damage to the heart, brain and kidneys, resulting in complications such as stroke, myocardial infarction. Hypertension requires pharmacological treatment such as the use of antihypertensive drugs. This study aims to analyze the relationship between self-care and medication adherence in hypertension sufferers. This research uses a quantitative correlational design method. The total sample was 30 respondents taken using consecutive sampling technique. Data was collected using a questionnaire, then univariate and bivariate analysis was carried out. Data were analyzed using Kendall's Tau-B correlation analysis. The results of bivariate analysis showed that there was no significant relationship between self-care and compliance with taking medication in hypertension sufferers (?: 0.319, p: 0.076). From the results of the research, it is recommended for future researchers to conduct further research on self-care and adherence to taking medication in hypertension sufferers because the results of this study show that there is no significant relationship between self-care and adherence to taking medication and it is hoped that the number of samples will be increased. Based on the research results, it is hoped that hypertension sufferers will pay more attention to self-care, especially when consuming antihypertensive drugs to avoid further complications.